Effect of regrinding dried distillers grains with solubles on finishing pig growth performance - J A De Jong; Michael D Tokach; Joel M DeRouchey; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2011)
A total of 1,235 barrows and gilts (PIC, 337 × 1050, initially 77.35 lb) were used in a 103-d study to determine the effects of regrinding dried distillers grains with solubles (DDGS) on finishing pig growth performance. Pigs were blocked by weight and randomly assigned to 1 of 2 treatments with 23 replications per treatment. Treatments included: (1) a corn-soybean meal diet with "normalâ€ DDGS (DDGS average particle size of 780 Î¼), and (2) the same corn-soybean meal diet with reground DDGS (DDGS average particle size of 691 Î¼). Diets were fed in 4 phases (77 to 117, 117 to 163, 163 to 196, and 196 to 270 lb for Phases 1, 2, 3, and 4, respectively). Phase 1 and 2 diets contained 40% DDGS, and Phase 3 and 4 diets contained 20% DDGS. To achieve uniform lots of DDGS among treatments, semi-loads were split in half and left either as-received or reground. The DDGS was reground using a RMS 9X36 dual roller mill with corrugations set at 6-6 on top and 13-13 on the bottom. Within each of the individual phases, there were no differences (P>0.18) in ADG, ADFI, or F/G. Similarly for the overall experiment, no differences (P<0.24) in growth performance were found. These data indicate that regrinding DDGS (95 Î¼ reduction in particle size) was not a large enough difference to affect growth performance; however, more research is needed to evaluate a greater reduction in particle size than achieved in the present study.; Swine Day, Manhattan, KS, November 17, 2011
Keywords: Swine Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-064-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1056; Swine; DDGS; Feed processing; Particle size; Finishing pig